2019
DOI: 10.3390/ijerph16152787
|View full text |Cite
|
Sign up to set email alerts
|

Public Perception of the Range of Roles Played by Professional Pharmacists

Abstract: Background: Professional pharmacists should be directly involved in patient healthcare as members of therapeutic teams are not the only dispensers of medication. Public perceptions of the professional role of pharmacists is expressed through patients’ attitudes, trust, and expectations as health and illness consultants, or qualified retailers of medicines. This perception is influenced by numerous determinants, both health-related and social. Objective: This research intends to describe the range of social rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 23 publications
0
16
1
1
Order By: Relevance
“…Meanwhile, effective health education requires establishing a proper consultative relationship with the patient (World Health Organization & Regional Office for the Eastern Mediterranean, 2012). Experiences from different countries suggest that the image of pharmacists gradually evolves, but patients may be unaware of these changes (Majchrowska et al, 2019). In Italy, for instance, a study published in 2003 showed that local pharmacists have only a small role in the education of patients because they go to the pharmacy mainly to buy medicaments (Bernardini et al, 2003).…”
Section: Subjective Normsmentioning
confidence: 99%
“…Meanwhile, effective health education requires establishing a proper consultative relationship with the patient (World Health Organization & Regional Office for the Eastern Mediterranean, 2012). Experiences from different countries suggest that the image of pharmacists gradually evolves, but patients may be unaware of these changes (Majchrowska et al, 2019). In Italy, for instance, a study published in 2003 showed that local pharmacists have only a small role in the education of patients because they go to the pharmacy mainly to buy medicaments (Bernardini et al, 2003).…”
Section: Subjective Normsmentioning
confidence: 99%
“…Meanwhile, although Polish patients still connect pharmacists mostly with selling medicaments [ 16 ], there are reports indicating patients’ positive attitudes and expectations for pharmacists’ advice or information on drugs, smoking cessation, and minor or chronic health conditions, including their screening and prevention [ 17 , 18 ]. The majority of Polish pharmacists also express positive attitudes and readiness to expand the scope of their practice [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, at the same time, they seem to have an unclear idea of their educatory role [ 19 ]. Moreover, the extent to which such services are actually provided remains unsatisfactory in the opinion of the majority of Polish patients [ 16 ]. Currently, there are no cognitive services implemented in Polish pharmacies, e.g., vaccinations or advice on smoking cessation services that would be financed by the public insurer.…”
Section: Introductionmentioning
confidence: 99%
“…In Malaysia, participants of a qualitative study viewed pharmacists mainly as suppliers of medication and had trouble envisaging their expanded roles as part of a healthcare team [27]. There is indeed an erroneous perception that a pharmacist's main role is dispensing, with many unaware of the enhanced roles of pharmacists such as providing PC services and managing long-term diseases [28][29][30][31][32][33][34][35][36] It has been postulated that this 'reductionist perception' [36] of pharmacists stems from the lack of interaction between patients and pharmacists at a higher level [35]. Where there is a lack of understanding of these expanded pharmacist roles, pharmacists can find it challenging implementing services and the ability of the profession for role expansion can be hindered [33].…”
Section: Discussionmentioning
confidence: 99%